LaplaceTransform
works on functions rather than equation. Taking a guess at what you want, we can solve for this Laplace transform in a couple of steps as below.
laplaceratfun =
LaplaceTransform[y''[t] - 2 y'[t] + y[t] - (1 + t), t,
s] /. {y[0] -> 1, y'[0] -> 0}
(* Out[1285]= -(1/s^2) - 1/s - s + LaplaceTransform[y[t], t, s] +
s^2 LaplaceTransform[y[t], t, s] -
2 (-1 + s LaplaceTransform[y[t], t, s]) *)
Solve[laplaceratfun == 0, LaplaceTransform[y[t], t, s]]
(* Out[1286]= {{LaplaceTransform[y[t], t, s] -> (
1 + s - 2 s^2 + s^3)/((-1 + s)^2 s^2)}} *)